Rancang Bangun Online Shop Pada Apotek Diana Berbasis Website - Yandra, Sidik Rama; Dewi, Ika Parma; Delianti, Vera Irma; Mursyida, Lativa (Jurnal Teknik Komputer dan Informatika, 2024)
In the rapidly evolving digital era, information technology has fundamentally transformed the way businesses operate. The utilization of the Internet and mobile devices has enabled businesses to create online platforms that facilitate business transactions more efficiently and provide greater accessibility to customers. Companies that fail to harness the potential of online business may miss valuable opportunities to reach customers and increase sales. To address these challenges, the author argues that a computerized system capable of addressing these issues is crucial. A solution is needed to streamline data processing and access while reducing error rates in the design of Diana Pharmacy's online store. The application's theme is crafted in the form of a program code to present a user-friendly interface with the system. Based on the results of the design of Diana Pharmacy's online store application, the availability of the website-based Diana Pharmacy online store will increase Diana Pharmacy's sales while benefiting Diana Pharmacy's customers. It is concluded that this occurs. This online store application is directly managed by the owner of Diana Pharmacy, and its data and confidentiality are maintained. An online store application tailored to the times, utilizing the functionality of payment gateways that facilitate the buying and selling process at Diana Pharmacy's online store.